VATS left upper lobectomy after CABG with LIMA-LAD bypass graft - Gabryel, Piotr; Piwkowski, Cezary; Zieliński, Paweł; Dyszkiewicz, Wojciech (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
Video-assisted thoracic surgery (VATS) lobectomy has been proven to be a safe operation associated with a low complication rate and good long-term results comparable to those obtained by the thoracotomy approach. During the development of thoracoscopic anatomical lung cancer resections, eligibility criteria for the operation have been gradually extended. Currently, even as complicated cases as bronchial and vascular sleeve resections or pneumonectomies are being performed by VATS. However, minimally invasive surgery after previous coronary artery bypass graft surgery merits special consideration due to the consequences of potential injury to the bypass graft. This is particularly important in the case of VATS left upper lobectomy after left internal mammary artery grafting to the left anterior descending artery bypass.